Legal Socialization For The Prevention Of Narcotics Abuse In Setanggor Village, Praya Barat District, Central Lombok Regency - Daulay, Fahmi Natigor; Suparidho, Febrihadi; Muhammad, Ade Sultan; Setiawan, Muhammad Rifaldi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Drug abuse has become a national problem that has spread to rural areas, including Setanggor Village, West Praya District, Central Lombok Regency, which has experienced an increase in drug cases. The low level of legal literacy among rural communities is a major factor that exacerbates this problem, where many people do not yet understand the provisions of Law No. 35 of 2009 on Narcotics along with its criminal sanctions. Community service activities in the form of legal socialization were carried out on August 25, 2025 using lecture methods and interactive discussions with the community and village officials. This program successfully increased public understanding of the definition of narcotics, classification of groups, health impacts, and legal consequences that users and dealers can receive. The enthusiasm of participants was evident from active participation in question and answer sessions, demonstrating the effectiveness of the program in increasing public legal awareness about the dangers of narcotics and the importance of early prevention.